“Addressing World’s Food –Security Demands Through Private Sector Led Management Systems In The Comesa Region To Enhance And Sustain Agro-Exports, For Economic Development” - Rwangoga, Deogratius (Archives of Business Research, 2019)
The paper is about addressing world’s food –security demands through private sector led management systems in the COMESA region to enhance and sustain agro-exports, for economic development. It follows a need to address best management measures that can easily be practical in nature. It advances the methodology of how such can be achieved in the COMESA region, as it calls for foreign direct investment into the region to contribute to economic growth . Exports of agriculture products are on high demand following a global post 2015 framework , that is a Rio+20 outcome document “THE FUTURE WE WANT” that calls for the interconnected nature of sustainable agriculture ,food security and nutrition as priorities for sustainable development . The world calls on Africa to be a world food basket and support ,enhance more sustainable agriculture food systems that are economically viable , so as to eradicate hunger , improve food security while conserving the natural resources . The papers discusses that since Abuja Treaty (1991) that institutes African Union , composed of 8 regional Blocks, Our COMESA Inclusive, COMESA as a regional is seen as the best Agricultural endowed among its member blocks , it could easily change the live hoods of its people through tilling the land and exporting the worldly demanded food, but it has not benefitted from this window , the reason the paper proposes the need for COMESA to partner with the private hands in the region to manage the food systems management and agro-exports than public agencies that are failing the service delivery . The proposal concludes that while it suggests the Private management of food-systems and Agro-exports, the governments must continue their drive for infrastructure development, industrialization policies and efforts to support conservation of natural resources and enhancing resilience to climate change and natural disasters. And concludes that while COMESA member countries have indeed continued the drive of togetherness in trade and come march 21, 2018 will launch the continental free trade area (CFTA) in Kigali –Rwanda, which was created in 2008 to boast trade integration , little efforts are seen for the region to position itself to fill the international welcoming aspect of Africa to lead in feeding the world. Hence with the COMESA realizing this and through the use of effective, timely and reliable means of the Private company for Management of Agro systems and Agro Export from COMESA region , we will for sure eradicate poverty, eliminate hunger and economically empower our populations and be respected as the proper service providers of the food source. Otherwise if we don’t be pro -active, I fore see, the re-colonization of Africa for Food so as to utilize the land left by our grandparents.